(untitled) (Portuguese Journal of Family Medicine and General Practice, 2005)
Introduction: Resistant hypertension is the failure to reach target blood pressure in patients receiving three anti-hypertensive drugs, including a diuretic, in full doses. Its prevalence ranges from 3 to 29%, and there are several factors that can contribute to it. A proper approach can identify these factors, reducing the proportion of patients that are resistant to the treatment. Aim: To present an updated review on causes of resistant hypertension and on strategies to lower its prevalence in family medicine consultation. Methods: A search using the keywords hard-to-control hypertension and resistant hypertension was performed among articles published between 1996 and 2004 indexed in MEDLINE, in a Portuguese medical journals database (Índex RMP) and in several international medical journal sites. Review: The main contributing factors to resistant hypertension are nonadherence, inadequate treatment, drug interactions, volume overload, secondary hypertension, pseudo-resistance, and other associated conditions (obesity-hyperinsulinemia, alcohol abuse, sleep apnea syndrome). Proper management of the patient with resistant hypertension includes an accurate anamnesis and a detailed physical exploration looking for signs of causes of secondary hypertension. Using this strategy its possible to detect in most cases the cause of resistance to treatment.